The 2007-2008 HarvestPlus Bangladesh Biofortified Rice Project Food Intake Dataset - International Food Policy Research Institute; University of California, Davis; International Centre for Diarrhoeal Disease Research, Bangladesh (International Food Policy Research Institute, 2017)
A multi-stage cluster survey was conducted in two rural rice-producing regions in Bangladesh in 2007-8 as the initial project of a HarvestPlus multi-stage research program to determine the potential impact of zinc-biofortified rice on the zinc and health status among children in Bangladesh who are at risk of zinc deficiency. The project protocol “Assessment of rice intakes and total dietary zinc intakes in rural Bangladesh” was conducted in collaboration with the University of California, Davis and the International Centre for Diarrhoeal Disease Research, Bangladesh (ICDDR,B). In each region, 240 children ages 24-48 months and their primary female caregiver were enrolled. Dietary information was collected primarily by direct observation and weighing of food preparation and consumption, including test weighing of milk intakes by breast-fed children. Height and weight were measured in all children and women, and in a subset of children, blood samples were collected and analyzed for concentrations of serum zinc and indicators of infection.